Relationship of employment status and socio‐economic factors with distress levels and counselling outcomes during a recession. Issue 2 (9th March 2018) - Berzins, Sandy; Babins‐Wagner, Robbie; Hyland, Kathleen
Abstract: Background: Social inequalities may be magnified during times of economic growth and recession when unemployment levels increase and income opportunities diminish. During a recession with high regional unemployment levels, can therapists expect the same improvements from therapy as they could in good economic times? The aim of this naturalistic study was to use routinely collected outcome measurement data to explore the relationships between unemployment status and client level of distress at the start and completion of counselling. Methods: The sample included 20, 690 clients from Calgary Counselling Centre (CCC) who received counselling between January 2013 and December 2016, and completed the Outcome Questionnaire‐45.2 (OQ) (Lambert, Gregersen & Burlingame, 2004) at both the first and last sessions. Relationships between employment status and level of distress at first and last counselling sessions for these clients were assessed using cross‐tabulations, chi‐square and one‐way analysis of variance tests of significance. Results: Less improvement was gained from counselling during the recession period than during the boom, and outcomes were affected by age, gender and income level differentially for employed and unemployed clients. Discussion: Routine outcome data can be utilised at an agency/community level to illustrate the effect of socio‐economic factors on mental health status and treatment outcomes in the general population as well as on community mental health service utilisation. Employment status affects the sociodemographic profile of clients attending a community mental health centre, which in turn affects counselling outcomes overall.